Glutamate dehydrogenase from Pantoea ananatis: A new bacterial enzyme with dual coenzyme specificity. - Maria S Kharchenko; Victoria S Skripnikova; Julia G Rostova; Natalia P Zakataeva (PLoS ONE)
Glutamate dehydrogenase (GDH) catalyzes the reversible conversion of α-ketoglutarate (α-KG) to L-glutamate (Glu) and plays an important role in linking nitrogen and carbon metabolism. However, little is known about this enzyme in the biotechnologically important bacterium Pantoea ananatis. In this study, we report for the first time the enzymatic characteristics of the P. ananatis AJ13355 GDH, GdhPa. GdhPa, a 46.5 kDa protein of the GDH50s group, was expressed in Escherichia coli host, purified, and biochemically characterized. In vitro enzymatic activity assays revealed that GdhPa is capable of catalyzing both the reductive amination of α-KG and the oxidative deamination of Glu with dual coenzyme specificity (NAD(H)/NADP(H)), a rare occurrence in bacterial GDHs. The NADH and NADPH specificity constants (kcat/Km) during reductive amination were similar (approximately 6 × 104), whereas the kcat/Km value for NAD+ was higher than that for NADP+ during oxidative deamination (9.96 × 103 vs. 1.18 × 103). The only gene encoding GDH in P. ananatis AJ13355 (gdhAPa) is located on the megaplasmid pEA320 and has a low level of expression when cells are grown under ammonium- and glucose-rich conditions, indicating that P. ananatis does not assimilate ammonium via GDH under these conditions. Our studies show that gdhAPa expression increases significantly when cells are grown (i) under low glucose concentrations; (ii) using Glu, L-proline (Pro), L-arginine (Arg), or L-histidine (His) as the sole source of carbon; or (iii) using Glu, Pro, Arg, or His as the sole source of both carbon and nitrogen. These findings indicate that the P. ananatis GDH catalyzes the oxidative deamination reaction in vivo. The results of this study provide new insights into the function of GDH in P. ananatis and serve as a basis for future studies on the molecular mechanisms underlying the regulation of GDH activity in this biotechnologically important bacterium.